Analysis of Educational Values in Tere Liye's ‘Hujan’ Novel as Literary Teaching Materials in High School - Lisa Rakhmanina; Melati Melati; Haimah Haimah (Edu-Ling: Journal of English Education and Linguistics, 2021)
Abstract The objective of this research was to gain a deep understanding of the educational values in Tere Liye's novel, Hujan. This novel, Hujan, served as the basis for the research. The novel's educational values served as the research's data. The research method was descriptive qualitative. According to the study, Tere Liye's novel Hujan reflects educational values for his readers in the following ways: first, the moral value of education: always help, perseverance, and responsibility. Second, there is the value of social education in terms of humanity, caring, and empathy. Third, there is the value of cultural education in terms of mutual cooperation, obedient rules, and mutual respect. Tere Liye's Hujan was suggested as an alternative to literary teaching materials in high school.